Autologous blood pleurodesis for the treatment of postoperative air leaks. A systematic review and meta‐analysis. Issue 20 (3rd September 2021) - Karampinis, Ioannis; Galata, Christian; Arani, Alireza; Grilli, Maurizio; Hetjens, Svetlana; Shackcloth, Michael; Buderi, Silviu; Stamenovic, Davor; Roessner, Eric D.
Abstract: Background: Postoperative air leaks are a common complication after lung surgery. They are associated with prolonged hospital stay, increased postoperative pain and treatment costs. The treatment of prolonged air leaks remains controversial. Several treatments have been proposed including different types of sealants, chemical pleurodesis, or early surgical intervention. The aim of this review was to analyze the impact of autologous blood pleurodesis in a systematic way. Methods: A systematic review of the literature was conducted until July 2020. Studies with more than five adult patients undergoing lung resections were included. Studies in patients receiving blood pleurodesis for pneumothorax were excluded. The search strategy included proper combinations of the MeSH terms "air leak", "blood transfusion" and "lung surgery". Results: Ten studies with a total of 198 patients were included in the analysis. The pooled success rate for sealing the air leak within 48 h of the blood pleurodesis was 83.7% (95% CI: 75.7; 90.3). The pooled incidence of the post‐interventional empyema was 1.5%, with a pooled incidence of post‐interventional fever of 8.6%. Conclusions: Current evidence supports the idea that autologous blood pleurodesis leads to a faster healing of postoperative air leaks than conservative treatment. The complication rate is very low. Formal recommendations on how to perform the procedure are not possible with the current evidence. A randomized controlled trial in the modern era is necessary to confirm the benefits. Abstract : A systematic literature review was conducted until July 2020 to detect the success rate of autologous blood pleurodesis in healing prolonged air leaks. Ten studies with a total of 198 patients were included in the meta‐analysis. The pooled success rate for sealing the air leak within 48 h of the blood pleurodesis was 83.7% (95% CI: 75.7; 90.3). The pooled incidence of the post‐interventional empyema was 1.5%.